Green Gentrification and Environmental Injustice: A Discussion Based on the New Pinheiros River Program, São Paulo, Brazil - Alves, Estela Macedo; Paz, Mariana Gutierres Arteiro da; Fracalanza, Ana Paula (Frontiers in Sustainable Cities, 2021)
Through the analysis of New Pinheiros River Program, São Paulo, Brazil, it’s considered the differences in the solutions presented to implement environmental projects in different territories over the same sub-basin. By one side, basic infrastructure for water depollution in most vulnerable neighborhoods upstream; by the other side, leisure, sports and cultural equipments at Marginal Pinheiros, already full of urban structure. General aim is to analyze the process of capitalist production of Pinheiros River depolluting program area, proposed by the São Paulo State government in 2019, as well as green gentrification and creation of environmental injustice. Methodology consists of bibliographic research, analysis of the Program’s documents and speeches of people in charge. Global South cities have been experimenting environmental injustice as result of financial capital investments.